2011
DOI: 10.1038/ejhg.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Children, biobanks and the scope of parental consent

Abstract: The use of stored tissue samples from children for genetic research raises specific ethical questions that are not all analogous to those raised when adult participants are concerned. These include issues with regard to consent, as it is typically a parent who consents to the use of samples from children. In this paper, we discuss the scope of parental consent. This scope has a temporal dimension and one related to the content of consent. It is not questioned that the temporal scope of parental consent is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…Parents believe that they have their child's best interest at heart, that they know their child best, and that they have the authority to decide whether their child should participate in research. [37] Whether their children would agree with their decisions is unknown. One study from Belgium found that adolescents generally were accepting of empowering parents on their behalf.…”
Section: Discussionmentioning
confidence: 99%
“…Parents believe that they have their child's best interest at heart, that they know their child best, and that they have the authority to decide whether their child should participate in research. [37] Whether their children would agree with their decisions is unknown. One study from Belgium found that adolescents generally were accepting of empowering parents on their behalf.…”
Section: Discussionmentioning
confidence: 99%
“…5,11,30 The consent should provide the information in a manner that allows the details of the research to be easily understood. The high percentage agreement by laypeople compared with other groups may be explained by thinking that children between 12 and 18 years old can readily understand the information.…”
Section: Consent For Children's Participation In Biobanksmentioning
confidence: 99%
“…The second dimension has to do with the question of whether parents have the right to consent to future unspeciWed research on the stored tissue samples of their children (socalled broad consent) under certain conditions (i.e. ethics review) or only to speciWc types of research (Hens et al 2011a).…”
Section: Consentmentioning
confidence: 99%
“…Therefore, children should be allowed to express their opinions on the type of research that is performed on their samples as they grow older. They suggest that parents can give consent for further unspeciWed research if such research aims to understand and treat diseases, but that if samples are used later on for research that is more sensitive, such as behavioral research or IQ-related research, participants should be recontacted for renewed consent (Hens et al 2011a). …”
Section: Consentmentioning
confidence: 99%